Sosialisasi New Normal Masa Covid-19 di Stasi Santo Fransiskus Assisi Lingga - Kurniason, Hugo Theo; Martinus, Martinus; Simbolon, Subandri; Palupi Handayani, Exnasia Retno; Brata Role, Metoddyus Tri; Erika, Teresia Giofani; Erismato, Erismato; Cendana Sari, Theresia Yovita (Amare, 2022)
The Covid-19 pandemic has brought its own challenges to some aspects of people’s religious life, especially in carrying out worship. People have difficulty understanding the pandemic in relation to the implementation of worship. At St. Francis of Assisi Lingga Station, Catholics have to follow directions from the government and the Church to worship from home. Their problem is the problem of this Community Service, how to deal with covid-19 in the Catholic faith? how to do worship from home? The method used is community service and socialization. The result of this service is that the station community gains a better understanding of the pandemic and gains insight into how to arrange pastoral and catechism activity in the midst of the Covid-19 Pandemic. With this understanding, the people are expected not to become Catholics who confused but to become more alive in the midst of pandemic.